The Role of Digital Literacy and Self Efficacy in Enhancing Students' Critical Thinking in Learning in the Digital Era - Ferdinand Salomo Leuwol; Deswalantri Deswalantri; Cindy Sandra Lumingkewas; Petrus Jacob Pattiasina; Budi Mardikawati (Universitas Muhammadiyah Enrekang, 2023)
This research is motivated by the low critical thinking skills of students. The purpose of this research is to examine and analyze the role of digital literacy and self-efficacy in increasing students' critical thinking in the digital era. This research uses a quantitative approach with a survey method. The sampling technique used purposive sampling of 100 students. The instruments used are tests and questionnaires. The data analysis technique used is the classical assumption, correlation analysis, and multiple linear regression analysis including hypothesis testing T test, F test and R2 test. The results of this study show 1) Digital literacy has a positive and significant effect on students' critical thinking in the digital era, 2) Self-Efficacy has a positive and significant effect on students' critical thinking in the digital era, and 3) Digital literacy and self-efficacy have a positive and significant effect and are significant to students' critical thinking in the digital era. The findings of this study hint at the importance of digital literacy and self-efficacy in increasing students' critical thinking in the digital era.